Evaluating the prevalence of second mesiobuccal canal in maxillary molars - A. Vahid; MR. Hamidi (Tehran University of Medical Sciences, 1995)
During the past century, valuable studies were done on maxillary mesiobuccal canals morphology. In general, knowing pulp-chamber floor is a great aid in finding extra root canals. Findings of invivo and invitro canals are highly different which implies difficulties in finding canals in clinical treatments. Therefore in this study by modifying access cavity preparation methods possible orifice areas are introduced. In an invitro analysis, 29% of first maxillary molars canals were found Type 3 and 35% Type 2 in radiographic view of mesiodistal aspect. In intra oral analysis, by modifying access cavity and removing mesial wall dentin, a high percent of these orifices are discovered.